Delayed vs initial cytomegalovirus prophylaxis after kidney transplantation. Issue 6 (6th April 2020) - Laub, Melissa R.; Byrns, Jennifer; Gommer, Jennifer; Ellis, Matthew; Harris, Matt
Abstract: It is recommended to start cytomegalovirus (CMV) prophylaxis within 10 days of solid organ transplant, if indicated. Our center underwent a cost‐savings initiative to delay CMV prophylaxis initiation from postoperative day zero to postoperative day 7 or upon discharge, hypothesizing this would not affect clinical outcomes but could impact costs. The purpose of this retrospective study was to determine the effects of early vs delayed (<72 vs >72 hours after transplant) CMV prophylaxis in kidney and kidney/pancreas transplant recipients transplanted between June 2014 and January 2017. The primary endpoint was incidence of CMV infection within 1 year. Secondary endpoints included CMV disease, CMV testing, and valganciclovir cost during index hospitalization. A total of 173 patients (114 early, 59 delayed) were included. CMV infection occurred in 61% vs 54% in the early vs delayed group ( P  = .5). Excluding low‐level DNAemia (QNAT < 200 IU/mL), infection occurred in 30% vs 22% in the early vs late group ( P  = .4). The median days to starting prophylaxis were 0 and 6 in the early and delayed group ( P  < .05), which led to a median cost savings of $497.00 per patient during index hospitalization ( P  < .05). Delaying prophylaxis initiation did not impact CMV outcomes in this cohort and decreased costs.